Elastase and alkaline protease production by Pseudomonas aeruginosa strains: comparison of two procedures - (:unkn) unknown (My University, 2002)
Pseudomonas aeruginosa is an opportunistic pathogen that can cause fatal infections in immunocompromised hosts. The virulence of P. aeruginosa is associated with the presence of various extracellular factors like elastase and alkaline protease. These enzymes are suggested to contribute to tissue destruction and assist bacterial invasion during infection. Therefore it seems likely that determination of these virulence factors will be an important prognostic marker in the near future especially for follow up of cystic fibrosis patients, to start antimicrobial agents that are directly or indirectly inhibit microbial growth or virulence factor production. Herein, we suggest a simple test procedure to be used in routine laboratories for estimation of elastase and alkaline protease levels and compare them with quantitative methods in the literature. We detected the amount of elastase and alkaline protease in 49 clinical P. aeruginosa isolates by comparing agar plate method and colorimetric assay. The resulting values were in the range reported in the literature and differed from one strain to another(elastase: 0-1390 mg/ml, alkaline protease: 0- 770 mg/ml). Linear relationships were found when assays compared in pairs and significant correlation coefficients were obtained(r>0.788 for alkaline protease, p<0.0001- r>0.926 for elastase, p<0.0001). Our method can be applied in laboratories regardless of the availability of technical equipment.
Keywords: Pseudomonas aeruginosa; Bacterial Proteins; Virulence; Metalloendopeptidases; Bacteriological Techniques; Serine Endopeptidases